Reinvestment decisions by entrepreneurs: Rational decision-making or escalation of commitment? - McCarthy, Anne M.; Schoorman, F.David; Cooper, Arnold C. (Journal of Business Venturing, 1993)
Among the most important decisions made by entrepreneurs are those relating to whether to expand, maintain, or contract their businesses. We would expect these major commitments to be based upon expectations about future performance; these expectations, in turn, would be heavily influenced by performance to date. Thus, we might presume that businesses that have been receiving favorable feedback from the marketplace would be more likely to expand, and those receiving negative feedback would be more likely to contract. Ongoing research in decision-making suggests that psychological processes may play a role in influencing these decisions. Under certain conditions entrepreneurs may be influenced by a phenomenon termed “escalation of commitment.” This may lead entrepreneurs to decide to expand the asset bases of their firms, regardless of feedback from the marketplace. The literature on escalation of commitment suggests that, under certain conditions, decision-makers who make an initial decision become overly committed to the original choice and then subsequently make decisions biased by psychological commitment. Previous research (most of which has been conducted in laboratory settings) suggests that escalation bias is more likely to occur (1) if entrepreneurs have started their firms (rather than purchased them): (2) if entrepreneurs have partners; (3) if entrepreneurs expect to use their skills in the new business; and (4) if entrepreneurs are overconfident (that is, expected to do substantially better than others in the same kinds of business). It is also expected that these “escalation predictors” will have a relatively greater influence when feedback is negative than when it is positive: the negative feedback seems to invoke a self-justification process. It is also hypothesized that the influence of these predictors will be less in the third year of a business than in the second year. Finally, it is expected that these psychological influences will help to provide systematic explanation of reinvestment decisions over and beyond what one could predict based upon financial feedback. The hypotheses were tested using data from a longitudinal study involving 1112 firms. It was found that entrepreneurs who had started their firms and those who had expressed substantial over-confidence were significantly more likely to make the decision to expand. The hypotheses that those who had partners and those who expected to apply their skills would be more likely to expand were not supported. Furthermore, and consistent with previous research, these psychological escalation predictors seemed to exert a greater influence when feedback from the marketplace was negative. As expected, there was a declining influence in the third year as compared with the second. Consistent with the prior literature and the hypotheses, these psychological predictors did show a small, but systematic influence upon reinvestment decisions. Decisions to expand or contract a business are not necessarily good or bad; however, it is important that entrepreneurs be aware of the factors influencing their decisions. Entrepreneurs should recognize that the escalation bias tendency is likely to occur. Seeking independent opinions from advisors who do not feel as much personal responsibility for the original decision to start may lead to more objective evaluation of alternatives. Advisors should also realize that the inclination to escalate exists and is natural; they may thereby be able to guard against the tendency to be swept along by the entrepreneur's enthusiasm and propensity to escalate. Entrepreneurs and their advisors (as well as researchers) should recognize that important entrepreneurial decisions are often influenced by psychological as well as economic factors. This awareness should enable entrepreneurs to make more rational decisions.